Superficial Circumflex Iliac Artery Perforator Flap Elevation Using Preoperative High-Resolution Ultrasonography for Vessel Mapping and Flap Design - Yoshimatsu, Hidehiko; Karakawa, Ryo; Fuse, Yuma; Hayashi, Akitatsu; Yano, Tomoyuki (Journal of Reconstructive Microsurgery, 2021)
Background The superficial circumflex iliac artery (SCIA) perforator (SCIP) flap has gained acceptance among reconstructive microsurgeons, the minimal donor site morbidity being its greatest advantage. The purpose of this article is to introduce the use of preoperative ultrasonography to facilitate elevation and to avoid postoperative complications of the SCIP flap.Methods Preoperative mapping of the SCIA and the superficial circumflex iliac vein (SCIV) using a high-resolution ultrasound system were performed in patients undergoing reconstruction using a free SCIP flap. The skin paddle was designed placing the SCIA and the SCIV in the middle of the flap.Results Preoperatively marked SCIA and SCIV were found intraoperatively in all cases. The skin paddle design for sufficient arterial inflow and venous drainage resulted in no postoperative flap complications.Conclusion The use of a preoperative high-resolution ultrasound system significantly facilitates elevation of the SCIP flap, notably via the following 2 points: 1) pedicle can always be found under the markings made with preoperative ultrasonography, 2) satisfactory perfusion of the flap can be guaranteed via a safe flap design that includes preoperatively marked vessels within the skin paddle.
Keywords: ultrasonography; superficial circumflex iliac perforator flap; flap design